2012
DOI: 10.1371/journal.pone.0041778
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Comparative Efficacy of Treatments and Controls for Depression

Abstract: BackgroundAlthough previous meta-analyses have examined effects of antidepressants, psychotherapy, and alternative therapies for depression, the efficacy of these treatments alone and in combination has not been systematically compared. We hypothesized that the differences between approved depression treatments and controls would be small.Methods and FindingsThe authors first reviewed data from Food and Drug Administration Summary Basis of Approval reports of 62 pivotal antidepressant trials consisting of data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
150
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(161 citation statements)
references
References 36 publications
4
150
0
7
Order By: Relevance
“…Although there are available treatments, there is still a large proportion of patients that do not respond satisfactorily to traditional antidepressant therapies (Khan et al, 2012). Many etiological factors could underlie depressive disorders, including alterations in monoaminergic function, but several studies have implicated dysregulation of the cholinergic system in depression in human subjects (Janowsky et al, 1972;Risch et al, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Although there are available treatments, there is still a large proportion of patients that do not respond satisfactorily to traditional antidepressant therapies (Khan et al, 2012). Many etiological factors could underlie depressive disorders, including alterations in monoaminergic function, but several studies have implicated dysregulation of the cholinergic system in depression in human subjects (Janowsky et al, 1972;Risch et al, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…According to WHO (2012) recommendations, the treatment options for moderate to severe depression consist of basic psychosocial support which is combined with either antidepressant medication or psychotherapy (WHO, 2012). A recent systematic review on the effect of different treatments for depression concluded that antidepressants or psychotherapy alone are not significantly different from alternative therapies, such as exercise, or active intervention controls (Khan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Best practice guidelines recommend a stepped-care approach to the treatment of MDD, with less intense interventions preceding more intensive treatment (American Psychiatric Association, 2010;NICE, 2009). Within a stepped-care approach, it is recommended that when patients do not respond to brief interventions, antidepressant medication be combined with structured psychological interventions (notably CBT), since the combination of these two treatment modalities leads to a lower relapse rate than either alone (Khan et al, 2012). With these research findings in mind, the SYTL program was developed as a treatment that combines effective CBT practices, interventions grounded in positive psychology, and principles of effective group therapy.…”
Section: Introductionmentioning
confidence: 99%